Repurchase Intention of Z-Generation in the Indonesian Marketplace - Yeyen Novita; Pandu Nur Wicaksono; Faiz Nasokha; Rifda Nabila (UIN Raden Mas Said Surakarta, 2022)
This study aimed to investigate the influence of e-service quality, customer trust, and word of mount on repurchase intention mediated by customer satisfaction. The sample in this study were taken by Z generation who had purchased products online in the marketplace. The number of samples that used were 200 respondens. Sampling using purposive sampling technique, namely the determination of the sample by selecting a group of subjects in accordance with this study. This study used primary data obtained from distributing questionnaires. The data obtained were analyzed by using SmartPLS 3.2.9 software. The results show that customer trust and e-service quality have a positive effect on customer satisfaction. Meanwhile the word of mounth has no effect on customer satisfaction. The results of the study also show that e-service quality, customer trust, and word of mount have a positive effect on repurchase intention. Meanwhile, customer satisfaction has no effect on repurchase intention. Furthermore, customer satisfaction is not able to mediate the relationship of e-service quality, customer trust, and word of mount to repurchase intention. The novelty of this research is that it involves respondents who are Z-Generation.